Disclosure about corporate social responsibility through ISO 26000 implementation made by Saudi listed companies - Lassaad Ben Mahjoub (Cogent Business & Management, 2019)
The paper examines the corporate social responsibility (CSR) reporting ‎conducted by Saudi listed firms based on the guidelines of ISO 26000. To measure the ‎extent of ISO disclosure, we use a content analysis. A CSR reporting index is ‎established throughout the global reporting initiative (GRI) and the ISO 26000’s seven ‎core subjects of social responsibility. These sources inform the measurement of the ‎level of CSR information reported in different documents (e.g., annual reports, ‎sustainable development reports, etc.) published by these companies during the period ‎‎2015–2017. ‎First, we conducted this study to explore the reactions of Saudi firms to the ‎implementation of the new ISO 26000, and we searched for the most significant ‎determinants of this reporting in Saudi listed companies. Second, we tested the ‎bidirectional link between CSR reporting through Saudi market information asymmetry. ‎The results showed that all the sampled firms included some ISO 26000 ‎reporting in their published documents. Nevertheless, most reporting levels were weak. ‎However, the results showed also a positive effect of CSR reporting based on ‎ISO 26000 on information asymmetry. ‎